Increased residual cardiovascular risk in U.S. veterans with moderately-elevated baseline triglycerides and well-controlled LDL-C levels on statins - Leatherman, Sarah; Ferguson, Ryan; Hau, Cynthia; Harrington, Kelly; Granowitz, Craig; Philip, Sephy; Toth, Peter Paul; Bhatt, Deepak; Boden, William (Frontiers in Cardiovascular Medicine, 2022)
Background Recent studies have demonstrated a causal role for elevated triglycerides (TG) in incident cardiovascular (CV) events in patients with established coronary heart disease (CHD) and those with CV risk factors alone, particularly diabetes. Objective Using a large cohort of U.S. veterans with statin-controlled LDL-C levels (40-100 mg/dL), we explored residual CV risk among patients with elevated baseline TG levels (150-499 mg/dL) versus those with normal TG levels (<150 mg/dL). Methods We identified veterans receiving a statin but not a TG-lowering agent from the VA electronic health records database, from 2010-2015. We compared composite CV event rates (MI, stroke, unstable angina, coronary revascularization, and CV death) between the elevated TG and normal TG groups. We stratified the study cohort according to 3 CV risk groups: 1) no diabetes and no prior CV event, 2) diabetes and no prior CV event, and 3) prior CV event. We calculated crude event rates, rate ratios, and event rate ratios adjusted for age, sex, systolic blood pressure, estimated glomerular filtration rate, and weight. Results The cohort included 396,189 veterans (predominantly male and white) of whom 109,195 (28%) had elevated TG levels. Those with elevated TG were younger (age 73 vs. 77 years) and had a higher body mass index (31.3 Kg/M2 vs. 28.3 Kg/M2). The overall composite crude and adjusted rate ratios comparing the elevated and normal TG groups were 1.10 (1.09, 1.12) and 1.05 (1.03, 1.06), respectively. For CV risk groups 1, 2 and 3, the adjusted rate ratios comparing the elevated and normal TG groups were 0.99 (0.96, 1.02), 1.05 (1.02, 1.08), and 1.07 (1.04, 1.10), respectively. An association of increased rate ratios did not hold for fatal events. Conclusion Those with elevated TG levels and well-controlled LDL-C on statins showed a modest increase in CV events compared to those with normal TG. Elevated TG levels were associated with increased CV events in patients with established CV disease and with diabetes only, suggesting that elevated TG levels are associated with a similar degree of residual risk in high-risk primary prevention and secondary prevention settings.